Perbandingan Hipertensi pada Masyarakat Yang Tinggal di Pesisir Pulau Maitara dan Daerah Dataran Tinggi Gurabunga Tidore - Eko Sudarmo Dahad Prihanto; Fitriani Giringan; Ratyh Jihan Fahira; Rahmawati M Kamal (Syntax Idea)
Hypertension is a commonly encountered disease in daily clinical practice, but often goes unnoticed by its sufferers. Complications can occur in various organs, with the most significant being complications affecting the heart. The environment plays a role in hypertension, where inhabitants living in coastal areas tend to suffer from hypertension due to high sodium consumption, while in highland areas, hypertension is more influenced by acute hyperbaric hypoxia conditions, although its pathophysiology is not yet precisely known. Various studies have yielded diverse results. North Maluku Province is an archipelagic region with a large coastal area, and no research has been conducted there, prompting this study. An analytical observational study was conducted using a cross-sectional approach, focusing on the population of hypertensive individuals residing in the coastal area of Maitara and the highland area of Gurabunga, Tidore. Samples were consecutively selected until the required sample size was met. Variables examined included gender, age, occupation, salt consumption patterns, body mass index, ancestry, alcohol consumption habits, systolic blood pressure, and diastolic blood pressure. Analysis was performed using an independent t-test when sample homogeneity conditions were met. Significant differences were found in some demographic-clinical variables. There was a significant difference in diastolic blood pressure between the Gurabunga area and the coastal area of Maitara, but no significant difference was observed in systolic blood pressure.